Afterword: Bending the Rules. (1st June 2021) - Stamatakis, Chris
Abstract: This afterword to 'Artes Poeticae: Formations and Transformations, 1500–1650' surveys some of the organizing themes and questions that bind the various chapters of this special issue of CRJ. Particular attention is paid to the various, arguably evolving, attitudes to rules inherited from or retrospectively sourced in classical antiquity by early modern writers and commentators. The afterword attributes much of the early modern contestation over rules to lexical minutiae in (principally) Aristotelian and Horatian poetics and considers how writers in the period 1500–1650 derive literary-critical capital from those moments when familiar categories and definitions break down.